Tracker Software Assisted Guided Inquiry Learning Model to Improve High School Students' Graphical Representation Ability - Aprilia, Ananda; Wijayanti, Pipit; Wilujeng, Insih; Aryono, Ichwan; Dwandaru, Wipsar (Universitas Negeri Semarang, 2025)
This research aimed to improve students' graphical representation using the guided inquiry learning model assisted by the Tracker software. The method used in this research was a pre-experimental study with a one-group pretest-posttest design. The data collection techniques used were observation, interview, and tests. The sample for this research was students of science class X at Public Senior High School. The analysis techniques were carried out using Wilcoxon and N-Gain test calculations. The results of the research showed that the Wilcoxon test produced a significance, which means that there were differences in the guided inquiry learning model assisted by Tracker software to improve the graphical representation abilities of high school students on the Work and Energy topic. The N-Gain test indicated that more than half of the students achieved a high category, while only a small number obtained the low category. Moreover, the N-Gain results for the two-question item indicators showed that most students were in the medium and high categories. Thus, students' graphical representation abilities can be improved using the guided inquiry learning model assisted by the Tracker software.